2012
DOI: 10.3174/ajnr.a3315
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MRI-Derived Apparent Diffusion Coefficients in Newly Diagnosed Gliomas with [18F]-Fluoro-L-Dopa PET: What Are We Really Measuring with Minimum ADC?

Abstract: BACKGROUND AND PURPOSE:There is significant interest in whether diffusion-weighted MR imaging indices, such as the minimum apparent diffusion coefficient, may be useful clinically for preoperative tumor grading and treatment planning. To help establish the pathologic correlate of minimum ADC, we undertook a study investigating the relationship between minimum ADC and maximum FDOPA PET uptake in patients with newly diagnosed glioblastoma multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
1
42
0
3
Order By: Relevance
“…Although these features were thought to likely coincide as high-grade tumors have greater cellularity, infiltration and proliferation, these findings suggest that other factors may contribute to low ADC and high uptake of 18 F-DOPA. For example, tumor ischemia and tissue-compression or tumor necrosis may affect ADC measures [40]. These discrepant results support the need for further investigation of the under pathophysiology reflected by each measure and emphasizes the value of using multi-parametric imaging over any single functional or physiological imaging measure to improve the accuracy of tumor characterization.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Although these features were thought to likely coincide as high-grade tumors have greater cellularity, infiltration and proliferation, these findings suggest that other factors may contribute to low ADC and high uptake of 18 F-DOPA. For example, tumor ischemia and tissue-compression or tumor necrosis may affect ADC measures [40]. These discrepant results support the need for further investigation of the under pathophysiology reflected by each measure and emphasizes the value of using multi-parametric imaging over any single functional or physiological imaging measure to improve the accuracy of tumor characterization.…”
mentioning
confidence: 68%
“…[37] Recent studies have also shown that 18 F-DOPA has similar tumor uptake compared with 11 C-MET and thereby has good correlation with WHO tumor grade and proliferation, confirmed pathologically by Ki-67. [39,40] However, a longer sustained uptake of 18 F-FDOPA is observed in the normal striatum, which raises a challenge in using 18 …”
Section: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
“…Our quantitative approach included the calculation of three ADC, the mean ADC, usually used in clinical and experimental settings, and the minimum and the maximum ADC. The rationale of calculating minimum ADC is based on the hypothesis that the area of minimum ADC would correspond to the highest cellular density regions, thus, to the most probable infected portion of the PFCs [29]. Indeed, the cut-off of the minimum ADC shows the highest sensitivity and specificity for both readers.…”
Section: Discussionmentioning
confidence: 99%
“…The association between increased cellularity and restricted water diffusion, estimated by MD, was investigated in several previous studies, [17][18][19] but the utility of this parameter was not always reconfirmed. 20,21 A weak correlation can be a result of concomitant MD increases caused by edema and micronecrosis in HGGs, and it remains to be shown if MK can add important diagnostic information. MK calculated from a conventional DKI sequence and MKЈ obtained by our fast method are distinct quantities, because they are estimated in a different way.…”
Section: Discussionmentioning
confidence: 99%